2005
DOI: 10.1096/fj.04-3401hyp
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine receptors set the pattern of activity generated in subthalamic neurons

Abstract: Information processing in the brain requires adequate background neuronal activity. As Parkinson's disease progresses, patients typically become akinetic; the death of dopaminergic neurons leads to a dopamine-depleted state, which disrupts information processing related to movement in a brain area called the basal ganglia. Using agonists of dopamine receptors in the D1 and D2 families on rat brain slices, we show that dopamine receptors in these two families govern the firing pattern of neurons in the subthala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 57 publications
1
36
0
Order By: Relevance
“…The effects of dopamine on synaptic transmission are modeled for striatum, STN, and GP. We specifically include effects in STN and GP because of the noted changes in coupling between these nuclei after experimental manipulations that alter tonic dopamine (Magill et al, 2001;Baufreton et al, 2005).…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of dopamine on synaptic transmission are modeled for striatum, STN, and GP. We specifically include effects in STN and GP because of the noted changes in coupling between these nuclei after experimental manipulations that alter tonic dopamine (Magill et al, 2001;Baufreton et al, 2005).…”
Section: The Modelmentioning
confidence: 99%
“…Their absence in the BG of Parkinson's disease patients (Brown et al, 2001) and increase in power during motor activity Cassidy et al, 2002) suggests that ␥-band oscillations are intimately related to normal motor behavior (MacKay, 1997). However, despite the anatomically identified feedback loop formed between STN and GP, the two nuclei seem decoupled in the healthy BG (Magill et al, 2000;Raz et al, 2000;Urbain et al, 2000;Baufreton et al, 2005). For example, slow (Ͻ1 Hz) cortical oscillatory activity is reflected in STN neuron output but not transmitted to GP neurons, except when dopamine has been depleted, yet, after removing both cortex and dopamine, some residual slow oscillatory activity remains in both nuclei (Magill et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Also a recent study of children on and off methylphenidate (a stimulant that amplifies the release of dopamine) found that children with DCD improved manual dexterity when they were on the drug [12]. However, in addition to the basal ganglia areas, other areas such as primary motor cortex (M1) and sensory motor cortex (S1) may also contribute to the motor behavior deficits as their circuitries are interconnected [3]. Adult brain images have shown a bilateral circuit of sensory and motor areas involved in the control of the fingertip forces during precision grip tasks [11].…”
mentioning
confidence: 99%
“…Baufreton et al, by means of in vitro electrophysiological recordings, sho w e d t h a t a c t i v a t i n g D 1 a n d D 2 d o p a m i n e receptors with D1 and D2 agonists promotes pace making at the level of the STN by increasing the firing frequency of neurons that exhibit tonic firing capacity and by changing firing in burst-competent and spontaneously burst-firing neurons. Moreover, they also showed that D5 dopamine receptors may potentiate burst-firing in STN neurons by modulating L-type calcium channels in the absence of dopamine (Baufreton et al, 2003;Baufreton et al, 2005). Finally, Loucif et al showed that dopamine clearly produces subthalamic membrane depolarisation leading towards an increase in firing rate.…”
Section: Role Of Dopamine At the Level Of The Subthalamic Nucleusmentioning
confidence: 99%
“…Taken together, the majority of the available in vivo data clearly suggest an excitatory effect of dopamine on STN neurons that is mediated via dopamine D1 receptors. DA Campbell et al, 1985Hassani et al, 1999DA Zhu et al, 2002aZhu et al, 2002bD2 -quinpirole Zhu et al, 2002aTofighy et al, 2003 D1/D5-SKF82958;SKF 81297 Baufreton et al, 2003DA Zhu et al, 2002bD2 -quinpirole Zhu et al, 2002a 2005 D1/D5-SKF38393 ; SKF82958; SKF 81297 Baufreton et al, 2005Loucif et al, 2008 In Vivo DA Campbell et al, 1985amphetamine Welchsler et al,1979 D1/D2 -apomorphine Brown et al, 1978Hassani et al, 1999 D1/D5 -SKF82958 Hassani et al, 1999D2 -quinpirole Hassani et al, 1999DA Mintz et al, 1986Ni et al, 2001 D1/D2 -apomorphine Trugmann et al,1993Kreiss et al, 1996 D1/D5-SKF38393 ; SKF82958 Ni et al, 2001Kreiss et al, 1996 D1/D5 -SKF82958 Hassani et al, 1999DA Ni et al, 2001 D2 -quinpirole Hassani et al, 1999Ni et al, 2001 D1/D5- SKF38393 Ni et al, 2001 Table 1. Overview of different publications regarding the effects of dopamine and its agonists on subthalamic activity in both intact and 6-OHDA lesioned rats.…”
Section: Role Of Dopamine At the Level Of The Subthalamic Nucleusmentioning
confidence: 99%